Elements Of Welfare In Job Satisfaction Of Special Education Teachers In Malaysia - et. al., Nor Fauziyana binti Mosbiran, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The welfare element is also part of the job satisfaction construct related to head teacher leadership. This statement suggests that, the welfare of teachers affects job satisfaction, based on its relationship with head teacher leadership. Although this element is not a key element that impacts the construct of teacher job satisfaction, it remains significantly related to head teacher leadership. Some researchers have also found that the relationship between head teacher leadership and teacher job satisfaction is at a weak level, in terms of teacher welfare. Several theories also explicitly discuss related elements of welfare in explaining teacher job satisfaction. Such theories basically state that welfare is a necessity for a person to achieve satisfaction in work. In examining these elements in influencing the job satisfaction of special education teachers, this qualitative study was conducted. This study involved 11 coordinators of special education integration program (PPKI) in the state of Johor, Malaysia as respondents. Guessors were interviewed and the results were transcribed before being analyzed. The findings of this study can be used as a reference for future researchers in examining the perception of the element of welfare in the job satisfaction of special education teachers.